ANALISIS KUALITAS LAPORAN KEUANGAN DAERAH SEBAGAI SALAH SATU SYARAT TERWUJUDNYA GOOD GOVERNANCE (Studi Kasus Pada Pemerintah Kabupaten Kediri) - Adisty Bramantyo Sahertian (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2015)
This study tries to identify the appropriateness of financial statement of the regency of Kediri with the qualitative characteristics of financial statement, to analyze the quality of the financial statement for the realization of good governance, and to give draft of solution for the government of Kediri in facing setbacks during the preparation of its financial statement. This qualitative descriptive research uses case study approach, where the data is collected through interviews. The standard used by the author is the qualitative characteristics of financial statement. It consists of four aspects: relevant, reliable, comparable, and understandable. The results of this study are (1) the government of Kediri has prepared its financial statement according to the qualitative characteristics of financial statement; (2) the government of Kediri needs to improve its effort in realizing good governance since issues of corruption and government’s fraud spread among the citizens; (3) the setbacks faced by the government of Kediri is corruption practices committed by its employees. The solution to be prepared is application of reward and punishment system for the government employees of Kediri. Keywords: quality of financial statement, qualitative characteristics, good governance, government of Kediri